Novel process for nitrite removal driven by S(IV): NOx absorption and reductive denitrification in smelting industry. (1st July 2022) - Li, Sichao; Xu, Haomiao; Gao, Qiangwen; Huang, Wenjun; Wang, Yongjun; Zhang, Anbang; Cheng, Can; Qu, Zan; Yan, Naiqiang
Graphical abstract: Highlights: A self-removal method of N element in NO2 − driven by S(IV) was developed. The key parameters of NO2 − reduced by S(IV) were investigated. The results of product analysis verified that NO2 − was reduced via self-made NH2 SO3 H to harmless N2 . Abstract: The absorption products of NO x by SO3 2− -contained solution are mainly NO2 − or NO3 − which may cause secondary pollution and increase difficulty for further disposal in wastewater. Conversion of NO2 − into N2 using S(IV) (HSO3 − /SO3 2− ) reduction is a promising method for denitrification, yet it is difficult to be realized under SO2 -rich conditions. Here, a self-removal method was put forward for N element conversion driven by S(IV) ions. The first step was the reduction of NO2 − into trisulfonic acid (NTS) or amine disulfonic acid (ADS). Followed that the NTS/ADS was hydrolyzed into NH2 SO3 H. Then the NO2 − was reduced to N2 by NH2 SO3 H. The experimental results indicated that such method guarantee a higher NO x absorption efficiency and the higher than 95% absorption products were NO2 − . When S(IV)/NO2 − was higher than 4.2, 95% of NO2 − was reduced to NTS or ADS, then further hydrolyzed into NH2 SO3 H with higher than 90% efficiencies. Moreover, the gas chromatograph-mass spectrometer (GC–MS) and ion chromatography (IC) results confirmed that the main products of the reactions between NO2 − and self-generated NH2 SO3 H were N2 and SO4 2− . This study provides a new route for the safety disposal of NO2 − in non-ferrous smelting industry.